Q-LAVHA: A flexible GIS plugin to simulate lava flows. (December 2016) - Mossoux, Sophie; Saey, Mathijs; Bartolini, Stefania; Poppe, Sam; Canters, Frank; Kervyn, Matthieu
Abstract: Q-LavHA is a freeware plugin which simulates lava flow inundation probability from one or regularly distributed eruptive vents on a Digital Elevation Model (DEM). It combines existing probabilistic and deterministic models and proposes some improvements to calculate the probability of lava flow spatial propagation and terminal length. Spatial propagation is constrained by the probabilistic steepest slope. Corrective factors are included to allow the flow simulation to overcome small topographical obstacles and to fill pits. The terminal length of the flow simulation can be determined based on a fixed length value, a statistical length probability function or based on the thermo-rheological properties of an open-channel lava flow. The impact of model parameters, background slope and DEM resolution on the accuracy of the simulations are discussed. The user-friendly interface and the flexibility of Q-LavHA makes it a tool applicable from long-term volcanic hazard assessment to short-term hazard forecasting. Highlights: Free, user-friendly plugin to simulate lava flow inundation probability. Q-LavHA flexibility allows to adapt to a large range of situations. Q-LavHA applicability is tested on Nyamuragira (DRC) and Etna (Italy) volcanoes. Simulates the emplacement of lava in a realistic way from different source types.